Elective appendectomy: clinical case and literature review - Mansilla, Sofía; Haro, Camila; Almada, Mario; Brito, Noelia; Muniz, Nicolás (Cirugía del Uruguay, 2023)
Introduction: inflammatory masses of appendiceal origin are infrequent, represent 3% of acute appendicitis. Its therapeutic management can be systematized in initial surgery or conservative treatment. the latter consists of exclusive antibiotic therapy, or associated with percutaneous drainage. it is an alternative to undertaking a demanding appendectomy, with the risk of not identifying the cecal appendix, visceral injury, and the need for conversion or extended resections. However, the absence of pathological diagnostic confirmation requires protocolized follow-up in order to rule out differential diagnoses of greater prognostic relevance. Objective: present the case of a patient who underwent conservative management and elective appendectomy. a bibliographic review was carried out in the databases: pubmed, cochrane library, scielo and lilacs. Discussion and conclusions: inflammatory masses of appendiceal origin represent a diagnostic and therapeutic challenge, requiring specific management and follow-up. The indication for elective appendectomy is controversial, it is considered in the presence of persistent pathological images and diagnostic doubts, or in patients with recurrent appendicitis